Woreda Participatory Land Use Planning for Pastoral Areas in Ethiopia - CGIAR Research Program on Livestock (2019)
The WPLUP process was developed and then piloted. Following additional stakeholder consultations the process was finalised and a two-volume manual produced. The manual was launched in 2019 by the Ministry of Agriculture, followed by trainings.